Reference Gene Selection for RT-qPCR Analysis of Flower Development in Chrysanthemum morifolium and Chrysanthemum lavandulifolium - Qi, Shuai; Yang, Liwen; Wen, Xiaohui; Hong, Yan; Song, Xuebin; Zhang, Mengmeng; Dai, Silan (Frontiers in Plant Science, 2016)
Quantitative real-time PCR (qPCR) is a popular and powerful tool used to understand the molecular mechanisms of flower development. However, the accuracy of this approach depends on the stability of reference genes. The capitulum of chrysanthemums is very special, which is consist of ray florets and disc florets. There are obvious differences between the two types of florets in symmetry, gender, histological structure and function. Furthermore, the ray florets have various shapes. The objective of present study was to identify the stable reference genes in Chrysanthemum morifolium and Chrysanthemum lavandulifolium during the process of flower development. In this study, nine candidate reference genes were selected and evaluated for their expression stability acrosssamples during the process of flower development, and their stability was validated by four different algorithms (Bestkeeper, NormFinder, GeNorm and Ref-finder). SAND(SAND family protein) was found to be the most stably expressed gene in all samples or different tissues during the process of C. lavandulifolium development. Both SAND and PGK (phosphoglycerate kinase) performed most stable in Chinese large-flowered chrysanthemum cultivars, and PGK was the best in potted chrysanthemums. There were differences in best reference genes among varieties as the genetic background of them were complex. These studies provide guidance for selecting reference genes for analyzing the expression pattern of floral development genes in chrysanthemums.